2017
DOI: 10.1016/j.jaac.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Parenting Program for Prevention and Early Intervention of Anxiety Problems in Young Children: Randomized Controlled Trial

Abstract: Results provide empirical support for the efficacy of online delivery of the Cool Little Kids program. Online dissemination may improve access to an evidence-based prevention program for child anxiety disorders. Clinical trial registration information-Randomised Controlled Trial of Cool Little Kids Online: A Parenting Program to Prevent Anxiety Problems in Young Children; http://www.anzctr.org.au/; 12615000217505.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 33 publications
5
72
0
Order By: Relevance
“…Although inclusion criteria allowed for parents of youth aged 0 to 18 years, participants of the included studies were parents or caregivers of young people who ranged in age from 12 months to 15 years. The majority of interventions catered to parents of youth aged under 5 years ( n = 12, Baker et al, ; Breitenstein et al, ; Day & Sanders, ; DuPaul et al, ; Hemdi & Daley, ; MacKenzie & Hilgedick, ; Morgan et al, ; Nixon et al, ; Sanders et al, ; Sanders et al, ; Sourander et al, ; Van Zeijl et al, ). The average number of participants across studies was n = 208.60, and ranged broadly from 33 to 916 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although inclusion criteria allowed for parents of youth aged 0 to 18 years, participants of the included studies were parents or caregivers of young people who ranged in age from 12 months to 15 years. The majority of interventions catered to parents of youth aged under 5 years ( n = 12, Baker et al, ; Breitenstein et al, ; Day & Sanders, ; DuPaul et al, ; Hemdi & Daley, ; MacKenzie & Hilgedick, ; Morgan et al, ; Nixon et al, ; Sanders et al, ; Sanders et al, ; Sourander et al, ; Van Zeijl et al, ). The average number of participants across studies was n = 208.60, and ranged broadly from 33 to 916 participants.…”
Section: Resultsmentioning
confidence: 99%
“…No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ). In most studies, the majority (>50%) of the sample were educated with post‐secondary qualifications ( n = 14, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; DuPaul et al, ; Fang et al, ; Hemdi & Daley, ; Jones et al, ; Khanna et al, ; Morgan et al, ; Sanders et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Yap et al, ). While most studies did not adequately report the employment status of their participants ( n = 14, DuPaul et al, ; Enebrink et al, 2012; Fang et al, ; Khanna et al, ; Kuravackel et al, ; MacKenzie & Hilgedick, ; Morawska et al, ; Morgan et al, ; Nixon et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schinke et al, 2009b; Sourander et al, ; Van Zeijl et al, 2006), of those that did, most reported over 50% of their sample engaged in employed work of some description ( n = 8, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; Hinton et al, ; Irvine et al, ; Sanders et al, ; Schwinn et al, ; Yap et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were Australian parents of 319 temperamentally inhibited young children recruited to the ‘Cool Little Kids Online’ early prevention trial who completed the final follow‐up questionnaire containing the OAPA (Morgan et al., ). These participants were recruited through preschool services and online advertising to take part in an Internet‐based parenting program to prevent anxiety disorders in young children.…”
Section: Methodsmentioning
confidence: 99%